Effect of D-Panthenol on Corneal Epithelial Healing after Surface Laser Ablation - Islam Mahmoud Hamdi (Journal of Ophthalmology)
Purpose. To study the effect of D-panthenol (provitamin B5) on corneal epithelial healing, in cases of surface laser ablation. Patients and Methods: 45 eyes, of 45 patients undergoing laser surface ablation, received D-panthenol 2% in one eye and artificial tear drops of similar composition not containing D-panthenol in the other eye, postoperatively, for 2 months. Patients were examined daily for 3 days after the procedure. They were then examined weekly for 1 month. An additional examination was made after 2 months. Visual acuity (Log MAR) was assessed at every visit. Rate of healing (% of covered area) and subjective sensation of discomfort (scale 0–5) were assessed in the 1st 3 visits. Residual manifest cylinder (D) (as a parameter of corneal irregularity) and corneal clarity (epithelial and stromal haze) were assessed from week 1 to month 2. Results. During the first 3 days, both groups showed statistically nonsignificant (P>0.05) results. From week 1 to month 2, eyes receiving D-panthenol showed better vision and less residual cylinder (P<0.05) at week 1. For all other parameters, and at different examinations, both groups showed a statistically nonsignificant (P>0.05) difference. Still, eyes receiving D-panthenol showed better values at the majority of the parameters tested. Conclusion. D-Panthenol effect on corneal epithelial regeneration is of minimal clinical relevance. A different dosage and a larger sample of patients might reveal a statistical relevance. This trial is registered with https://doi.org/10.1186/ISRCTN81441126.